Gestão de projetos: evolução do conhecimento nos eventos científicos na área de administração e engenharia da produção no brasil e sua aplicação prática - Santos, Tatiana Céu Silveira (2013)
The objective of analyzing the evolution of scientific knowledge in project management of the articles featured in Brasilian major scientific events in the areas of Management and Engineering in the last 12 years - from 2000 to 2011, and is established as the perception of professionals with the practical application of this discipline. Through a bibliometric analysis of publications were consulted in the annals ENANPAD, ENEGEP SEMEAD, SIMPOI and SEGET. This study also includes a field research in the area of professional project management in order to capture their opinion on the use of this discipline on professional practice. As a whole, the research aims to evaluate the intensity of scientific research and the market, identifying which are the most handled issues and their possible shortcomings. It is to highlight the main themes, authors, social network, methodological approaches, the primary references and the authors who contributed most to the area, and identify the research area addressed more, both in academic conferences as well as in area of professional practice, particularly in the areas of administration and production engineering. The method used is exploratory and descriptive, qualitative and quantitative approaches. Through literature review and interviews with the participation of professionals working in the area of project management, we sought to investigate whether these knowledge areas incorporate Project Management as a discipline in its theoretical and applied scientific research and professional practice . The results demonstrate that project management is a discipline that still has a great field to mature both in terms of scientific tract as professional practices, which reinforces the need for their study of systematic dissemination.